Increasing Shareholders Value through NPV-Negative Projects - Paweł Mielcarz; Paweł Paszczyk (Contemporary Economics)
The concept of Net Present Value (NPV) is a widely accepted tool for verification of financial rationality of planned investment projects. Projects with positive NPV increase a company's value. Similarly, those with negative NPV lead to a decline in the value of a business. This article attempts to answer the question: are projects with negative NPV always disadvantageous in terms of maximization of shareholder value and when should an NPV-negative project be considered justified? The authors discuss the issues of project valuation depending on different conditions. First, they briefly summarize the main idea of valuation - the aim of every company is to maximize shareholder value. Contemporary professional texts say that the way to achieve this goal is through projects that can generate a positive Net Present Value. When there are no such investments within reach, the company should pay dividends to its owners. The authors claim that some circumstances justify investments with a negative Net Present Value, as they still produce maximum possible shareholder value. The three model situations where this takes place are: (1) tax on dividends; (2) shareholders' perception of risk; and (3) temporary inefficiency of the markets. Taxes on dividends reduce cashflows for shareholders from distributed dividends. Therefore, they act exactly as an investment with a negative NPV. The authors conclude that this creates an opportunity to maximize shareholder value by comparing this loss with available alternate projects with negative NPV. If the loss of worth, caused by such taxes, is bigger that the negative NPV of possible investments it will be more rational to invest instead of paying dividends. And, according to the authors, a project with a negative NPV leads to maximized shareholder value. In the second situation, the authors point out that some projects may have negative fundamental (intrinsic) value when valuated by the market (diversified owners) because of their higher expected rate of return. In the same circumstances, an undiversified shareholder may have a different perception of the investment. It is highly possible that he would be ready to accept a lower rate of return in exchange for more safety for his capital. The authors conclude that negative fundamental value (based on the market situation) may be of importance for such shareholder as he prefers projects with lower risk and a lower rate of return. Temporary inefficiencies of the markets may produce a risk of bankruptcy or liquidity problems. The authors argue that NPV-negative projects may be a way to free additional cashflows, which will allow the financial restructuring of the company.